ANALISIS PENGARUH KEPUASAN KERJA, REWARD DAN ADVERSITY QUOTIENT TERHADAP KINERJA DRIVER OJEK ONLINE - Untung Widodo; Lies Indriyatni; Yuliati .; Susanti Wahyuningsih (STIE Pelita Nusantara Semarang, 2022)
This study aims to determine whether Job Satisfaction, Reward and Adversity Quotient influence the performance of Online Ojek Drivers. The population in this study is Online Ojek Drivers in the city of Semarang. Sampling was carried out using the purposive sampling method and the number of samples was 126 respondents. The type of data used is primary data. This study uses a questionnaire in collecting data. The test techniques used are validity test, reliability test, classic assumption test including normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing in this study used multiple linear regression analysis and hypothesis testing with the help of IBM SPSS statistics 23. The results of this study indicate that job satisfaction has a positive and significant effect on the performance of online ojek drivers. Reward has no positive and insignificant effect on the performance of Online Ojek Drivers. Adversity Quotient has a positive and significant effect on the Performance of Online Ojek Drivers. Job Satisfaction, Reward and Adversity Quotient together or simultaneously have a significant effect on Driver Online Performance.